Analisis Yuridis Normatif Putusan Pencabutan Jabatan Notaris Tanpa Pemberian Salinan Akta (Putusan Ptun Nomor: 235/G/2019/PTUN.KT) - Alfika Salsa Qurrotulaini; Komariah Komariah; Yohana Puspitasari Wardoyo (Indonesia Law Reform Journal, 2022)
A notary is a public official who has the authority to make an authentic deed, which is specifically licensed by the government to sign a document. As a notary, it is necessary to adhere to the guidelines, authority, and code of ethics when carrying out their duties, so that there is no violation of the code of ethics in carrying out their profession. The problems raised in this study are to find out how the process of revocation of a position in a notary is in the right way in accordance with the regulations of Law Number 30 of 2004, the position of a notary, and to find out and examine how to resolve the Administrative Court Decision Number: 235/G/2019/ PTUN.KT. The research method used in this research is normative juridical, namely research with literature studies using primary legal data and secondary legal materials. Based on the results of the study that in carrying out their duties, Notaries must obey and obey the professional code of ethics and be used as guidelines in carrying out their duties, namely the Law on Notary Positions No. 2 of 2014 concerning amendments to Law No. 30 of 2004 concerning Notary Positions. If a notary commits a violation of the code of ethics that is a serious violation, it can be proposed to give sanctions by being dismissed from his position in a dishonorable manner by the Minister at the suggestion of the Central Supervisory Council. Regarding the issuance of a ministerial decree, it is also necessary to apply the General Principles of Good Governance so that there is no cancellation of a disputed object decision because it does not issue the precautionary principle and the need to act according to the principle of accuracy in making a decision. So if there is an annulment of a decision made by the Minister of Law and Human Rights on a State Administrative Decision, it is necessary to have the responsibility to restore and restore the dignity of the Notary whose position is revoked.